2022
DOI: 10.3389/fimmu.2022.821730
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic SARS-CoV-2 Infection Is Associated With Higher Levels of Serum IL-17C, Matrix Metalloproteinase 10 and Fibroblast Growth Factors Than Mild Symptomatic COVID-19

Abstract: Young adults infected with SARS-CoV-2 are frequently asymptomatic or develop only mild disease. Because capturing representative mild and asymptomatic cases require active surveillance, they are less characterized than moderate or severe cases of COVID-19. However, a better understanding of SARS-CoV-2 asymptomatic infections might shed light into the immune mechanisms associated with the control of symptoms and protection. To this aim, we have determined the temporal dynamics of the humoral immune response, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 108 publications
0
28
0
Order By: Relevance
“…Among these genes, the expression of circadian rhythm proteins Period 2 and matrix metalloproteinase‐10 (MMP‐10) exhibited the most significant upregulation and downregulation, which was confirmed by RT‐qPCR analysis (Figure 6A,C ). The MMP‐10 expression pattern is conserved between humans and mouse, 40 and its expression is higher in asymptomatic COVID‐19 patients than in patients with reported symptoms, 41 indicating the role of MMP‐10 in anti‐SARS‐CoV‐2 infection. In the biological processes of Gene Ontology enrichment analysis, the growth‐related processes of cells were the most enriched in DEGs, such as the developmental process, multicellular organizational process, and collections structure development.…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, the expression of circadian rhythm proteins Period 2 and matrix metalloproteinase‐10 (MMP‐10) exhibited the most significant upregulation and downregulation, which was confirmed by RT‐qPCR analysis (Figure 6A,C ). The MMP‐10 expression pattern is conserved between humans and mouse, 40 and its expression is higher in asymptomatic COVID‐19 patients than in patients with reported symptoms, 41 indicating the role of MMP‐10 in anti‐SARS‐CoV‐2 infection. In the biological processes of Gene Ontology enrichment analysis, the growth‐related processes of cells were the most enriched in DEGs, such as the developmental process, multicellular organizational process, and collections structure development.…”
Section: Resultsmentioning
confidence: 99%
“…This disease has caused more than 552 million cases and 6.3 million deaths as of July 1, 2022 [ 15 ]. In four transcriptome datasets (GSE152075 [ 16 ], GSE157103 [ 17 ], GSE161731 [ 18 ], and GSE198449 [ 19 ]) for COVID-19 patients, VTP values were significantly greater in COVID-19 patients than in normal controls ( P < 0.01) ( Figure 2(a) ). Notably, in GSE157103, VTP values were significantly greater in intensive care unit (ICU) COVID-19 patients than in non-ICU patients ( P < 0.001) ( Figure 2(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on COVID-19 deceased patients confirmed regeneration of damaged lung epithelium following infection, while others showed extensive alveolar damage and lung fibrosis ( 16 ). That such regeneration may in part at least be actively imposed early on as a virus washout mechanism is suggested by a study that compared asymptomatic cases to patients with symptoms and detected 7 analytes (IL-17C, MMP-10, FGF-19, FGF-21, FGF-23, CXCL5 and CCL23) that were higher in asymptomatic infection ( 119 ). These are known to be involved in tissue repair.…”
Section: Inflammation: Sars-cov-2 Infection As a Case Studymentioning
confidence: 99%